Another Country : Queer Anti-Urbanism. - Herring, Scott, 1976- (Sexual cultures., 2010)
The metropolis has been the near exclusive focus of queer scholars and queer cultures in America. Asking us to look beyond the cities on the coasts, Scott Herring draws a new map, tracking how rural queers have responded to this myopic mindset. Interweaving a wide range of disciplines--art, media, literature, performance, and fashion studies--he develops an extended critique of how metronormativity saturates LGBTQ politics, artwork, and criticism. To counter this ideal, he offers a vibrant theory of queer anti-urbanism that refuses to dismiss the rural as a cultural backwater. Impassioned and pr.